MODELS OF STRATEGIC COMMUNICATION FOR ENSURING SOCIAL COHESION IN DE-OCCUPIED REGIONS - Tetiana Lushahina (Публічне управління та регіональний розвиток)
The article is devoted to the study of strategic communication models that contribute to strengthening social cohesion in the de-occupied regions of Ukraine. The aim of the study is to identify effective strategic communication models to support population cohesion in de-occupied areas, overcome the consequences of the informational and social divide caused by occupation, and facilitate the restoration of trust in state institutions and the formation of a shared civic identity. The research employs general scientific methods and an interdisciplinary approach. The analysis revealed the absence of a unified definition of the term «strategic communication», which has led to a wide range of interpretations and conceptual approaches. It is proposed to consider strategic communication as a key instrument of state policy in the context of hybrid threats and post-conflict transformation. For its effective implementation in de-occupied regions, it is essential to rely on well-founded theoretical frameworks and to take into account the specific characteristics of target audiences, particularly their value orientations, cultural background, and the psychological trauma they may have experienced. The study demonstrates that the effectiveness of strategic communication in de-occupied territories largely depends on the localization of messages, engagement of credible opinion leaders, inter-institutional coordination, and the long-term nature of information efforts. It is concluded that strategic communication functions not only as a tool for delivering information but also as a mechanism for social recovery, integration, and societal consolidation. Furthermore, it is emphasized that a strategic communication model aimed at ensuring social cohesion in de-occupied regions cannot be universal for all communities, as the recovery process in each community has its own distinct features shaped by local conditions, historical experiences, and socio-cultural factors. At the same time, such a model may be based on a unified recovery algorithm that provides a general framework for communication strategies and is further adapted to the specific needs, values, and context of each individual community.